Experimental Study On The Wing Structure And Skin Flexibility For Flapping Wing Of Micro Aerial Vehicle (MAV) - Rashid, Rohayati Ab (2011)
Micro Aerial Vehicle (MAV) in Malaysia is still at an early stage. Therefore, the development of flapping a wing MAV by Aerodynamic Laboratory in School of Mechanical Universiti Sains Malaysia, encourage the local researchers and scientist to study the importance and the capability of flapping a wing MAV. The flapping wing MAV shows great promise in civilian and military applications as it possesses good maneuverability at low speeds and relatively good energy efficiency. Hence, it is vital for the MAV to be able to carry a certain load of additional equipment in accordance to performing its function successfully.